Polygamy: The possibly significant behavior of Aedes Aegypti and Aedes Albopictus in relation to the efficient transmission of dengue virus - Choochote W. (2014)
The polygamous behavior of male Aedes aegypti (L.) and Ae. albopictus (Skuse) was investigated by co-habiting a newly-emerged male and females in a 30 cm3 cage (1 male: 20 females) for up to 5 consecutive days. As determined by insemination rates, the results indicated that one Ae. aegypti and Ae. albopictus male could successfully mate with 1.10 (0-4), 4.10 (1-8), 5.40 (4-8), 5.10 (2-8), 5.15 (3-9) and 0.20 (0-3), 1.70 (0-3), 2.35 (1-4), 2.30 (0-4), 2.35 (1-4) Ae. aegypti and Ae. albopictus females, respectively on day 1,2,3,4 and 5 consecutively. The possibly significant role of their polygamy in relation to dengue virus transmission is discussed.